The Life of Tondo Kingdom in 9th Century: An Analysis of the Binatbát na Tansô ng Laguna Inscription - Yuwono, Ardi Tri; Vicaldo, Vengadcruz; Luz Bulaklak, Mariposa (Universitas Muhammadiyah Surakarta, 2025)
The discovery of the Binatbát na Tansô ng Laguna inscription in 1989 has significantly altered perspectives on the historical and prehistoric periods within Philippine historiography, as well as on the influence of external cultures on the development of cultural practices in the Philippine archipelago during the precolonial era. The inscription was composed in Old Malay and incorporates several lexical items from Old Javanese, indicating the influence of Old Malay and Old Javanese cultures during the precolonial period in the Philippines. The Binatbát na Tansô ng Laguna was issued by the Kingdom of Tondo in the year 900 CE (822 Saka). This study aims to examine the life of the people of the Tondo Kingdom in the 9th century through the lens of the Binatbát na Tansô ng Laguna inscription. The research employed historical methods with a qualitative approach. The inscription reflects a complex society with a hierarchical structure, as evidenced by titles such as senāpati and references to debt forgiveness, indicating the existence of an established legal and economic framework. From a linguistic perspective, the Binatbát na Tansô ng Laguna reveals substantial influence from Old Malay and Old Javanese cultures, particularly through the use of Old Javanese script and Sanskrit loanwords, suggesting strong trade and diplomatic interactions with other kingdoms such as Śrīvijaya and Medang. The term sang pamgat mḍang clearly links Tondo to the Medang Kingdom, while senāpati di tuṇḍu underscores Tondo’s local adaptation of administrative concepts originating from beyond the Philippine archipelago.